Muscle-Bone Interactions in Chinese Men and Women Aged 18–35 Years - Meihua Su; Zhaojing Chen; Breanne Baker; Samuel Buchanan; Debra Bemben; Michael Bemben (Journal of Osteoporosis)
To characterize bone mineral density (BMD), bone strength, muscle and fat mass, and muscle strength and power in Chinese women (n = 25) and men (n = 28) classified as in the bone accrual phase (18–25 years) or in the peak bone mass phase (26–35 years). Calcium intakes, physical activity levels, and serum vitamin D were measured. Dual-energy X-ray absorptiometry (DXA) assessed body composition, lumbar spine, and hip areal BMD (aBMD) variables and peripheral quantitative computed tomography (pQCT) assessed cortical and trabecular volumetric BMD (vBMD) and bone strength. Muscle strength and power were assessed by grip strength, leg press, and vertical jump tests. Calcium, serum vitamin D, and physical activity levels were similar across age and sex groups. Significant sex differences p<0.05 were found for most body composition variables, hip aBMD, tibia variables, and muscle strength and power. Adjusting for height and weight eliminated most of the significant sex differences. Women showed stronger positive correlations between body composition and bone variables (r = 0.44 to 0.78) than men. Also, correlations between muscle strength/power were stronger in women vs. men (r = 0.43 to 0.82). Bone traits were better related to body composition and muscle function in Chinese women compared to Chinese men aged 18 to 35 years, and peak bone mass seems to be achieved by 25 years of age in both Chinese men and women since there were no differences between the two age groups.